Analisis keandalan, kepastian dan penerimaan teknologi terhadap penggunaan kartu kredit pemerintah - Yadnya, I Dewa Gede Sayang Adi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Electronic transactions in government operational activities are carried out strictly and comply with regulations on both sides, namely financial transaction regulations regulated by government authorities and state financial management regulations. Strict management of electronic transactions, especially government credit cards, is carried out to prevent fraud, create reliable financial reports and protect against the risk of loss to the apparatus and the state. This study aims to analyze the factors that influence the interest in using KKP by government officials. The method used in this research is quantitative method using online questionnaires to credit card users who work in government units/organizations in the territory of Indonesia. Researchers used the Partial Least Squares (PLS) approach with Smart PLS to test the above assumptions based on SEM. The results of this study indicate that the p value <0.05 with a positive beta value which indicates that the good reliability of government credit cards will affect the effectiveness of user satisfaction. So that the reliability and certainty of government credit cards affect user satisfaction. In addition, it is known that the satisfaction of government credit card users is able to strengthen the relationship between perceived convenience and perceived usefulness.